Pelatihan Kepemimpinan Dalam Mitigasi Bencana Untuk Pemuda Marbot Masjid di Jawa Barat Melalui Kegiatan IDA Camp - Lulus Setiawan, Wawan (LPPM Universitas Koperasi Indonesia, 2024)
Disaster mitigation training for the Indonesian people is a must because Indonesia is in a disaster-prone area. This training is intended to provide community understanding and preparedness in anticipating, dealing with, and resolving the impacts of disasters. In the three stages of disaster-related activities, the role of leadership is important, because in a disaster situation, the community is in a critical situation and tends to panic. Youth, especially marbots, are a community that has the potential to be mobilized to act as leaders in disaster situations.